2018
DOI: 10.1063/1.5017827
|View full text |Cite
|
Sign up to set email alerts
|

A two and three-dimensional CFD investigation into performance prediction and wake characterisation of a vertical axis turbine

Abstract: The emergence of tidal energy as a key renewable energy source requires the development of computational design models for accurate prediction of turbine performance and wake effects whilst also being computationally efficient. In this paper, we develop and validate a three-dimensional CFD model for vertical axis turbines, which achieves high accuracy. We also investigate the limitations of two-dimensional models and present a blockage correction for improved prediction. The two-dimensional blockage correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…the sum of the bluff body and turbine entrance areas), and ∞ is freestream velocity. More detail on the experimental testing is available in Mannion, et al (2018a). Reproduced with permission from Mannion, et al (2018a).…”
Section: Device Background and Experimental Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…the sum of the bluff body and turbine entrance areas), and ∞ is freestream velocity. More detail on the experimental testing is available in Mannion, et al (2018a). Reproduced with permission from Mannion, et al (2018a).…”
Section: Device Background and Experimental Testingmentioning
confidence: 99%
“…1. Turbine position: the present turbine location relative to the static parts of the device was chosen based on experimental studies of flow acceleration around the bluff body (Mannion, et al 2018a) which found that maximum localised flow acceleration occurred at the widest point of the bluff body. To investigate whether this is indeed the optimum position for the turbine, two models are used where the turbine is moved downstream from its present position by 100 mm and 200 mm (parallel to the flume).…”
Section: Design Iterations Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a main result, the presence of winglets predicted in all considered cases an improvement in turbine efficiency which was estimated in around 20% for a symmetric hybrid fence-raked winglet regarding the straight blade case. Mannion et al [28] implemented 3D CFD simulations of a tidal turbine using ANSYS Fluent v17 and the SST turbulence model in both versions, standard and transitional. Meshes of up to 22 million elements where used reporting satisfactory grid convergence.…”
mentioning
confidence: 99%